2017
DOI: 10.1039/c7ra01524k
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of inorganic draw solutes on the performance of thin-film composite forward osmosis membrane in a microfiltration assisted anaerobic osmotic membrane bioreactor

Abstract: The influences of inorganic draw solutes on the performance of the thin-film composite forward osmosis (TFC-FO) membrane in microfiltration (MF) assisted anaerobic osmotic membrane bioreactors (AnMFOMBRs) were investigated in this study. The results indicated that compared to sodium chloride (NaCl) at the same osmotic pressure, magnesium chloride (MgCl 2 ) led to a higher flux decline of the TFC-FO membrane, induced by more severe membrane fouling. In addition, the NaCl and MgCl 2 had no impacts on the rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The OMBR FO channel was characterized by a very high TOC removal efficiency 98%during all four experimental runs. TOC removal obtained in this study agrees with other TFC-FO membrane bioreactor studies due to high rejection by the membrane in combination with bacterial biodegradation (Hu et al, 2017;Wang et al, 2014a) In this study, TOC removal in the bioreactor is shown to be affected by the oxic-anoxic cycle times; 86% TOC removal was observed in Run 1, 88% in Run 2, on average 92% Run 3 and 4, respectively. TOC concentrations in the MF permeate were observed to steadily decrease from 10.3 to 5.9 mg/L throughout all runs.…”
Section: Total Organic Carbon Removalsupporting
confidence: 89%
“…The OMBR FO channel was characterized by a very high TOC removal efficiency 98%during all four experimental runs. TOC removal obtained in this study agrees with other TFC-FO membrane bioreactor studies due to high rejection by the membrane in combination with bacterial biodegradation (Hu et al, 2017;Wang et al, 2014a) In this study, TOC removal in the bioreactor is shown to be affected by the oxic-anoxic cycle times; 86% TOC removal was observed in Run 1, 88% in Run 2, on average 92% Run 3 and 4, respectively. TOC concentrations in the MF permeate were observed to steadily decrease from 10.3 to 5.9 mg/L throughout all runs.…”
Section: Total Organic Carbon Removalsupporting
confidence: 89%
“…This phenomenon can be explained with two hypotheses, namely: (1) Greater ammonium permeability of the TFC membrane compared to the CTA one (one order of magnitude higher); and (2) high negative zeta potential of the TFC membranes, which is at a similar level to that of a cation exchange membrane (cation exchange like mechanism). Other articles with TFC membranes provide the same interpretation [21,25], but one study [14] explains the poor cation retention due to the Donnan equilibrium and the use of sea salt as a draw solute. The high concentration of NaCl in the draw solution and the higher diffusion coefficient of Na + compared to Cl − leads to a higher amount of Na + in the feed solution, creating a charge imbalance between the feed and draw solutions.…”
Section: Resultsmentioning
confidence: 96%
“…Although promising, this configuration presents several challenges due to its high fouling propensity and lower reversibility, which were shown to result in a significant decrease of the water flux (Jw). Also, to tackle the salt accumulation due to reverse solute flux (RSF) and the consequent inhibition of the anaerobic biomass, the addition of microfiltration and the use of expensive salts as draw solutes were required previously [12,13,14]. As such, incorporating an FO membrane within the biological reactor appears challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the high TAN rejection is the use of MgCl 2 as a draw solution: Hu et al attributed this to the Donnan equilibrium (Hu et al, 2017): Reverse salt diffusion of Cl -− ions exceeds that of Mg 2+ ions (Table 2,). This causes a charge imbalance and is prompting anions to diffuse from the feed solution to the draw solution in order to restore the charge equilibrium and leads to an accumulation of NH 4 -N in the feed.…”
Section: Nutrient Rejectionmentioning
confidence: 99%